egarding the calculation of the minimum friction stress in combined sewer pips - A V Kalinin (RUDN Journal of Engineering Research, 2012)
Based on the M.I. Aleksejev's conclusions about the influence of the friction losses coefficient on the longitudinal and cross pulsations momentary rate in the fluid, was derived a formula for minimum friction stress definition on the walls of the combined sewer and drainage pips. The analysis of sediment grain-size composition of pollutants in combined sewer systems of European cities is given. Performed an analysis of correspondence between calculated friction stress values and friction losses coefficient values, that were obtained from measurements in combined sewer systems of Paris and Nantes. Maximum diameters of the particles of pollution which will be weighed by runoffs in compliance with the rules accepted for disposal networks in Europe and the U.S are determined.